Evaluation Performance of Iterative Algorithms for 3D Image Reconstruction in Cone Beam Geometry - Al-anbari, Noor H. Fallooh; Al-Hayani, Mohammed H. Ali (Al-Nahrain Journal for Engineering Sciences, 2017)
Algebraic reconstruction technique (ART) is iterative reconstruction algorithm using for reconstructing the two dimension (2D) and three dimension (3D) images. In this research different algorithms of ART were used to reconstruction : (simple ART, Simultaneous ART, and Multiplicative ART) for reconstruction 3D image using multi slice scanner in cone beam geometry. To perform the time reconstruction of ART algorithms, use the Maximum-Likelihood Expectation Maximization (ML-EM) algorithm to fast ART algorithm. Multi slice Computed Tomography CT scanner newly discovered and used widely in the medical field for diagnosis and radiographic to its benefit from the speed of scanner and quality of image reconstruction comparing with single slice scanner. In simulation result the Multiplicative ART (MART) algorithm with suitable relaxation parameter